Regional disparity in epidemiological characteristics of adolescent scoliosis in China: Data from a screening program - Huang, Jiaoling; Zhou, Xuan; Li, Xin; Guo, Haibin; Yang, Yuqi; Cheong, I. O. Hong; Du, Qing; Wang, Hui (Frontiers in Public Health, 2022)
and eastern China and the dominant factors underlying these disparities. Methods: This cross-sectional study used data from a school scoliosis screening program conducted in two typical areas: Yangpu District of Shanghai (eastern China) and Tianzhu Tibetan Autonomous County of Gansu Province (western China), during October 2020 to February 2021. Participants included adolescents aged 12–16 years (4,240 in Shanghai and 2,510 in Gansu Province). School scoliosis screening data were obtained on age, sex, height, weight and BMI, and region as well. We screened angles of trunk rotation in level of proximal thoracic (T1–T5), main thoracic (T5–T12) and lumbar (T12–L5) by the forward bend test with scoliometer. An angle of trunk rotation ≥5° was used as the criterion to identify suspected scoliosis. Results: The proportion of suspected scoliosis was lower in Shanghai (6.9%) than in Gansu (8.6%). Angle of trunk rotation tended to increase with age in Shanghai, peaking at 15 years, but decreased with age in Gansu, and bottomed at 15 years. The angle of trunk rotation in the proximal thoracic, main thoracic, and lumbar part of the spine appeared to be larger in Gansu adolescents and in Shanghai female adolescents. Age was a relevant factor in angle trunk rotation in regression models and interacted with region as well. Conclusions: We found regional and age- and sex-related disparities in rates of suspected scoliosis.